Modified Dual-Energy Algorithm for Calcified Plaque Removal: Evaluation in Carotid Computed Tomography Angiography and Comparison With Digital Subtraction Angiography. Issue 11 (November 2017) - Mannil, Manoj; Ramachandran, Jaychandran; Vittoria de Martini, Ilaria; Wegener, Susanne; Schmidt, Bernhard; Flohr, Thomas; Krauss, Bernhard; Valavanis, Antonios; Alkadhi, Hatem; Winklhofer, Sebastian
Abstract : Objectives: Computed tomography angiography (CTA) is a valuable tool for the assessment of carotid artery stenosis. However, blooming artifacts from calcified plaques might result in an overestimation of the stenosis grade. The aim of this study was to investigate a new dual-energy computed tomography (DECT) technique with a modified 3-material decomposition algorithm for calcium removal in extracranial carotid artery stenosis. Materials and Methods: In this retrospective, institutional review board-approved study, 30 calcified carotid plaques in 22 patients (15 men; mean age, 73 ± 10 years) with clinical suspicion of stroke were included. Dual-energy computed tomography image data were obtained using second-generation dual-source CT with tube voltages at 80 and 140Sn kVp. Conventional CTA and virtual noncalcium (VNCa) images using the modified DECT algorithm were reconstructed. By assessing spectral characteristics, the modified DECT algorithm allows for a selective removal of calcium independent of blooming. Two independent and blinded readers evaluated subjective image quality, blooming artifacts, amount of (residual) calcification, and performed stenosis measurements according to the North American Symptomatic Carotid Endarterectomy Trial (NASCET) criteria. Differences were tested using a pairwise sign test. Paired sample t tests with Bonferroni correction ( P < 0.017) and Bland-Altman analyses were used to test for differences in carotid stenosis measurements between VNCa and conventional CTA using digital subtraction angiography (DSA) as the standard of reference. Results: Subjective image quality was similar among conventional CTA and VNCa image data sets ( P = 0.82), whereas blooming artifacts were significantly reduced in VNCa images compared with conventional CTA ( P < 0.001). Residual calcifications in VNCa images were absent in 11 (37%), minor in 12 (40%), medium sized in 2 (7%), and large in 5 (17%) arteries. Stenosis measurements differed significantly between VNCa (mean NASCET stenosis: 27% ± 20%) and conventional CTA images (mean NASCET stenosis: 39% ± 16%; P < 0.001) and between conventional CTA and DSA (23% ± 16%, P < 0.001). No significant differences in stenosis measurements were observed between VNCa and DSA ( P = 0.189), with narrow limits of agreement (mean difference ±1.96 standard deviations: −4.7%, −35.1%, and 25.7%). Conclusions: A modified 3-material decomposition DECT algorithm for calcium removal was introduced, which allows for an accurate removal of calcified carotid plaques in extracranial carotid artery disease. The algorithm might overcome the problem of overestimation of calcified stenosis due to blooming artifacts in conventional CTA.